Predominance of Wolbachia endosymbiont in the microbiota across life stages of Bactrocera latifrons (Insecta: Tephritidae) - Yong, Hoi Sen; Song, Sze Looi; Chua, Kah Ooi; Lim, Phaik Eem (Elsevier, 2017)
The Solanum fruit fly Bactrocera latifrons is an important agricultural pest. There is no report on the microbiota associated with this fruit fly. This study reports the bacterial communities associated with the life stages of this fruit fly from Malaysia. Illumina MiSeq next-generation sequencing of PCR-generated amplicons of 16S rRNA gene revealed the presence of different number of bacterial OTUs in the life stages studied. The number of bacterial OTUs at different taxonomic levels in the larva sample was much higher than in the adult male and adult female samples. The class Alphaproteobacteria of phylum Proteobacteria was predominant across the life stages studied (98.64% in the larva sample, 98.53% in pupa, 97.66% in adult male, and 99.89% in adult female). At the specific level, Wolbachia endosymbiont of Culex quinquefasciatus Pel was detected in all the life stages studied – 98.61% in the larva sample, 98.18% in pupa, 97.59% in adult male, and 99.88% in adult female. The ubiquitous presence of Wolbachia infections across life stages provides evidence for transmission from the larva stage to emerging adults. The role(s) of Wolbachia in B. latifrons remain to be determined.